Discovery of treatment for nerve agents targeting a new metabolic pathway - Trevor Glaros; Elizabeth S. Dhummakupt; Gabrielle M. Rizzo; Ethan McBride; Daniel O. Carmany; Linnzi K. M. Wright; Jeffry S. Forster; Julie A. Renner; Ruth W. Moretz; Russell Dorsey; Mark R. Marten; Walker Huso; et al. (Archives of Toxicology, 2020)
The inhibition of acetylcholinesterase is regarded as the primary toxic mechanism of action for chemical warfare agents. Recently, there have been numerous reports suggesting that metabolic processes could significantly contribute to toxicity. As such, we applied a multi-omics pipeline to generate a detailed cascade of molecular events temporally occurring in guinea pigs exposed to VX. Proteomic and metabolomic profiling resulted in the identification of several enzymes and metabolic precursors involved in glycolysis and the TCA cycle. All lines of experimental evidence indicated that there was a blockade of the TCA cycle at isocitrate dehydrogenase 2, which converts isocitrate to α -ketoglutarate. Using a primary beating cardiomyocyte cell model, we were able to determine that the supplementation of α -ketoglutarate subsequently rescued cells from the acute effects of VX poisoning. This study highlights the broad impacts that VX has and how understanding these mechanisms could result in new therapeutics such as α -ketoglutarate.